Collective Competencies and their Constitutive Elements: a case study in a Brazilian Fashion Group - Luiz Henrique da Silva; Tatiana Ghedine (BBR: Brazilian Business Review)
This article aims to identify the constitutive elements and main collective competencies (CC) in the Lunelli Group Creation Center's work teams, a business group focused on the fashion industry from the state of Santa Catarina in Brazil. Through exploratory and qualitative research, applying the case study strategy, conducted semi-structured interviews (with 36 employees from 6 work teams of the Lunelli Group's brands), and realizing a participant observation. The results demonstrate that the main CC, identified based on their constitutive elements, were the capacities to cooperate, create, planning collection, decision-making, solve problems, approval collection, and meet goals. We believe that these CC will allow organizations to understand teams' collective activities better, making it possible to develop the disabled CC and form the absent CC necessary to improve the team's performance and contribute to the organizational results.